Proton magnetic resonance spectroscopy (MRS) in individuals with internet gaming - McGlade, Erin C.; Han, Doug Hyun; Kim, Sun Mi; Shi, Xianfeng; Cline, Kirsten; Yurgelun-Todd, Deborah; Renshaw, Perry F. (Frontiers in Psychiatry, 2022)
Background Various comorbid psychiatric diagnoses, including attention deficit hyperactivity disorder (ADHD), have been reported in individuals with internet gaming disorder (IGD). Prior research has shown alterations in brain metabolites, including N-acetylaspartate (NAA), and combined glutamate and glutamine in patients with ADHD that were similar to those observed in patients with IGD. We hypothesized that the decreased NAA levels in the IGD group would be associated with a history of ADHD. Methods Forty adults participated in this study. Participants were classified as having a high risk for IGD if they had a total score higher than 21 on the Internet Gaming Disorder Scale-short form. Proton magnetic resonance spectroscopy (1H-MRS) and high-resolution structural magnetic resonance imaging (MRI) data were acquired using a 3 Tesla Siemens Prisma scanner system. Results Levels of NAA within the right prefrontal cortex were lower in the IGD group than those observed in the control group. In a multiple linear regression analysis, internet addiction test scores and history of ADHD were shown to predict increased game play. In addition, history of ADHD predicted lower levels of NAA within the right prefrontal cortex. Conclusion The preliminary results of current study suggest a mediating effect of ADHD on the severity of internet game play as well as the levels of NAA within the dorsolateral prefrontal cortex. The inclusion of ADHD in IGD research is important and deserving of further consideration.